Ionic Liquid-Mediated TiO2/Ag/CA Photocatalyst for Enhanced Water Remediation - Devagi, Kanakaraju; Feniellia Diwvya, Kutiang; Danielson, Ngo Joseph; Lim, Ying Chin; Micky, Vincent (Elsevier B.V., 2024)
The effect of an environmentally friendly green solvent template, ionic liquid (IL) - 1-butylimidazolium acetate on the surface area of TiO2 and its further combination with silver (Ag) dopant and cellulose acetate (CA) support were evaluated together. In this study, the TiO2/Ag/CA photocatalyst was synthesized and systematically investigated for the degradation of dyes. The incorporation of IL during synthesis led to a notable increase in the surface area of TiO2 (174.8 m2/g) and TiO2/Ag/CA (186.5 m2/g) photocatalyst, as evidenced by Brunauer Emmett Teller (BET) surface analysis. The findings revealed that TiO2/Ag/CA photocatalyst (IL: 3 mL, Ag: 2 wt%, CA: 0.5%) exhibited great efficiency in removing both individual and mixed dyes (MB, MO and RhB) under UV irradiation (λ = 365 nm) and visible light (λ = 440 nm) after 120 min. The antibacterial activity of TiO2-1/Ag 2%/CA 0.5% investigated via disc diffusion method against Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus) bacteria demonstrated inhibition zones, indicating the antibacterial effectiveness of the photocatalyst. With the imperative goal of eliminating chemical pollutants and undesired biological constituents from wastewater, the TiO2/Ag/CA photocatalyst investigated in this study exhibits the capability to effectively tackle both challenges with a high degree of efficiency.